Selective facet joint and interlaminar fusion using unilateral biportal endoscopy for thoracolumbar compression fractures: a comparative study - Bo Zheng; Peng Li; Xiu-Li Zhang; Hao Zhou; Ze-Bi He (Scientific Reports)
Abstract To compare the clinical outcomes and radiological findings of selective facet joints and interlaminar fusion using UBE technique with percutaneous pedicle screw fixation (observation group, OG) versus open reduction fusion fixation (control group, CG) in patients with thoracolumbar compression fractures. 110 patients were included, including 56 in the OG and 54 in the CG. The clinical results were evaluated by visual analogue scale score (VAS) and the oswestry disability index score(ODI). Radiographic findings were evaluated by the sagittal cobb angle(CA), the anterior vertebral height(AVH) and the sagittal index(SI). The amount of blood loss and hospitalization days in the OG were significantly lower than those in the CG( p < 0.05). The VAS, ODI, CA, AVH, and SI scores significantly improved after operation in both groups (p < 0.05). Compared with the CG at 1 day and 1 week after operation, OG patients’ VAS score significantly improved ( p < 0.05). 1 week after operation, CA in OG was significantly higher than that in CG( p < 0.05). Selective facet joints and interlaminar fusion using UBE technique combined with percutaneous pedicle screw fixation versus open reduction fusion fixation have achieved good clinical and radiographic results for the treatment of compression thoracolumbar fractures, including improved pain and disability, corrected kyphotic deformity, restored vertebral height, and minimal complications. Additionally, with UBE technology, there is less blood loss, more early back pain relief, and shorter hospital stay.